PENGARUH MODEL PROJECT BASED LEARNING (PjBL) TERHADAP HASIL BELAJAR PESERTA DIDIK PADA PEMBELAJARAN TEMATIK DI MADRASAH IBTIDAIYAH - Wati, Nia (Titik Fokus Karya, 2024)
The selection of appropriate learning models significantly influences student learning outcomes, especially in thematic learning. This research focuses on the application of the Project-Based Learning (PjBL) model to improve learning outcomes for third-grade students at MIN 4 Tabalong. The background of this research is based on the observation that conventional teacher-centered learning models during the pandemic led to lower student engagement and academic performance. A quantitative approach was employed, using a pre-experimental method with a one-group pretest-posttest design. The research sample consisted of 24 students. Data were collected through pretests and posttests, analyzing the effect of the PjBL model on student outcomes. The results showed a significant improvement in students' learning outcomes after the application of the PjBL model. The pretest results indicated that 45.83% of students were classified as “very good,” and the posttest results showed 100% of students in this category. The Wilcoxon test further confirmed that the PjBL model had a significant positive impact on students’ learning outcomes (p = 0.000 < 0.05).